Factors determining long-term success of biologic therapy in rheumatoid arthritis - Dmitry Evgenyevich Karateev (Современная ревматология, 2015)
The necessity to achieve clinical remission or low disease activity in every patient with rheumatoid arthritis highlights the importance of combination therapy with methotrexate and biological agents for treatment of resistant to conventional disease-modifying anti-rheumatic drugs patients. Modern requirements mean not only the achievement of results but also long-term maintaining of success. The possibility to get stable results of treatment is determined by many factors such as: clinical efficacy, safety, low immunogenicity, persistence on therapy and the economic feasibility. Analysis of published data for last 5 years leads to the conclusion that etanercept has an optimal combination of these parameters among inhibitors of tumor necrosis factor alpha.